Shelter from the Storm: Upgrading Housing Infrastructure in Latin American Slums - Sebastián Galiani; Paul J. Gertler; Ryan Cooper; Sebastián Martínez; Adam Ross; Raimundo Undurraga (Inter-American Development Bank (IDB), 2014)
This paper provides empirical evidence on the causal effects that upgrading slum dwellings has on the living conditions of the extremely poor. In particular, we study the impact of providing better houses in situ to slum dwellers in El Salvador, Mexico and Uruguay. We experimentally evaluate the impact of a housing project run by the NGO TECHO which provides basic pre-fabricated houses to members of extremely poor population groups in Latin America. The main objective of the program is to improve household well-being. Our findings show that better houses have a positive effect on overall housing conditions and general well-being: treated households are happier with their quality of life. In two countries, we also document improvements in children's health; in El Salvador, slum dwellers also feel that they are safer. We do not find this result, however, in the other two experimental samples. There are no other noticeable robust effects on the possession of durable goods or in terms of labor outcomes. Our results are robust in terms of both internal and external validity because they are derived from similar experiments in three different Latin American countries.
hdl:11319/6561
Keywords: I12; I31; J13; O15; O18; 330; Slums; Housing; Health; Happiness; Internal and External Validity